Failure analysis of a run-of-the-river hydroelectric power plant. (October 2016) - Teran, L.A.; Roa, C.V.; Muñoz-Cubillos, J.; Aponte, R.D.; Valdes, J.; Larrahondo, F.; Rodríguez, S.A.; Coronado, J.J.
Abstract: One of the challenges posed by hydraulic energy generation stems from the exploitation of hydrological resources that carry significant amounts of sediment that erodes the surfaces of turbines. This is the case for the Amaime hydroelectric plant, which is located in the western mountainous region of Colombia and was seriously affected by sediment after a brief period of operation. The main symptom indicating failure was a rise in the temperature of the bearings caused by an increase of almost two bars in the pressure between the cover on the side of the generator and the runner, which was caused by the wearing of the seal labyrinths. Inspections that were carried out after six months of operation indicated that there was a 300% increase in the clearance between the covers and the runner, which caused a higher axial thrust on the bearing. The inspections verified that severe wear had occurred on important elements of the turbine, such as the runner, guide vanes and turbine covers, which required major repairs to the two generation groups of the plant in less than 2 years, which is a much shorter time between repairs than is recommended by international standards. Analyses of the material, medium, particles and the worn surfaces demonstrated that the wear on the turbine was mainly due to erosion by hard particles, which was caused by the high sediment concentration and the low hardness of the material used to construct the turbine. Highlights: A Francis turbine affected by sediment erosion was analysed. Due to wear in the turbine, several of its components were seriously affected. The time of service of the turbine until the failure was too short. It was found that hard particles and construction materials led to failure.